Global Bollywood : travels of Hindi song and dance - Gopal, Sangita; Moorti, Sujata, 1963- (University of Minnesota Press, 2008)
This interdisciplinary collection describes the many roots and routes of the Bollywood song-and-dance spectacle. Examining the reception of Bollywood music in places as diverse as Indonesia and Israel, the essays highlight the cultural influence of Hindi film music from its origins to today. Contributors: Walter Armbrust, Anustup Basu, Nilanjana Bhattacharjya, Edward K. Chan, Bettina David, Rajinder Dudrah, Shanti Kumar, Monika Mehta, Anna Morcom, Ronie Parciack, Biswarup Sen, Sangita Shrestova, Richard Zumkhawala-Cook.